Reproductive Cycle, Size at Maturity and Fecundity of Giuris margaritaceus in Limboto Lake - Lamadi, Arafik; Iranawati, Feni; Sriwidodo, Maheno; Wiadnya, Dewa Gede Raka (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research The size of the first mature gonads in hulu'u fish can be analyzed. Differences in sperm and egg size characterize sexual maturity. Sexual maturity is not influenced by season. Hulu'u fish have an asynchronous spawning type. Abstrack Understanding fish reproduction biology, particularly sexual maturity, the reproductive cycle, and fecundity, is useful for managing fisheries. The reproduction of Giuris margaritaceus in Limboto Lake is regrettably unknown. Over a year, fish specimens (N = 662) were gathered. They ranged in length from 6.5 to 20.9 cm (mean SD 10.9±2.5). Fecundity varied from 30,057 to 61,920. The first sexual maturity of male and female fish occurred at different sizes, 11.2 cm and 10.3 cm, respectively. This information is needed to determine this fish's lowest acceptable harvest length under the management aim to enter all-female fish for reproduction at least once. We estimated the reproductive of G. margaritaceus cycle using the size of the oocytes, histological analysis of the ovaries, and monthly mean GSI. These techniques produced the same reliable conclusion: G. margaritaceus can spawn yearly, with maximal between September and October. Based on this finding, spawners of Giuris margaritaceus can be kept from entering the reproductive stock between September and October. Future efforts to fine-tune fishing efforts for the effective management of G. margaritaceus may be aided by the study's findings.